189 Efficiency of utilizing standardized ileal digestible Thr for whole body protein retention in pregnant gilts during early, mid and late gestation. (7th December 2018) - Navales, R; Dunn, J; Htoo, J; Touchette, K; Thaler, R; Levesque, C
Abstract: A total of 45 gilts (165.7 ± 13.6 kg, 39.1 ± 2 d of gestation) were used in a 3-period N-balance study to evaluate the efficiency of utilizing SID Thr for whole body protein retention in gestating gilts. Gilts were randomly assigned to one of 4 diets set to provide 60, 70, 80 and 90% of the model-predicted daily SID Thr requirement for protein retention (NRC, 2012) at d 41–52 (6.46 g/d, Period I), d 68–79 (6.05 g/d, Period II) and d 96–107 (9.75 g/d, Period III) of gestation. Diets contained 3300 kcal/kg ME and 11.6% CP and given at a rate of 2.13 kg/d in Periods I and II and 2.53 kg/d in Period III to ensure energy was not limiting the response to Thr. The 12-d balance period was based on total urine collection using urinary catheters and determination of fecal N-digestibility using indigestible marker. Daily Thr retention was estimated based on NRC (2012) prediction of Thr content in each gestation pools. Thr efficiency (kSID Thr) was calculated as the ratio of daily Thr retention and daily SID Thr intake. Data were analyzed as RCB with diet as the fixed effect. The linear and quadratic response in whole-body N and Thr retention was tested within each balance period. Whole-body N and Thr retention were not affected by the dietary SID Thr levels for Periods I and II. In Period III, there was a linear increase ( P <0.001) in whole body N and Thr retention. Efficiency of Thr use in period I, II, and III ranged from 0.22 to 0.32, 0.41 to 0.52, and 0.51 to 0.59, respectively. The lack of response in whole body protein retention in Periods I and II and the decreasing kSID Thr may in part reflect excess Thr intake. Efficiency of Thr use does not appear to be constant throughout gestation.